The logic of religion - Dougherty, Jude P., 1930- (Catholic University of America Press, 2003)
The logic of religion presents an examination of the nature of religion from a philosophical perspective. In successive chapters classical, medieval, and modern authors are canvassed for their views. Even among those who find no evidence for the existence of God, we encounter discussions of the nature of religion and its function in society. This study begins in antiquity with Socrates, Plato, Cicero, and Seneca. It then moves through Augustine to the Middle Ages as represented by Averroes and Aquinas. By so proceeding, the author gives the reader insight into the nature and logic of religion as conceived before and after the advent of Christianity. Subsequent investigation leads to a consideration of the work of David Hume, Immanuel Kant, and G.W.F. Hegel, in whose philosophies we find not only an account of the logic of religion but an appreciation of its implications in the practical order, and of Sigmund Freud's negative assessment of religion in The future of an illusion. Although the focus of this study is primarily Western religion, attention is also paid to selected oriental modes of thought, some properly called "religion" in the Western sense, others more akin to philosophy than religion.